Chemoenzymatic synthesis of novel N‐(2‐hydroxyethyl)‐β‐peptoid oligomer derivatives and application to porous polycaprolactone films. Issue 8 (24th December 2013) - Monsalve, Leandro N.; Petroselli, Gabriela; Erra‐Ballsells, Rosa; Vázquez, Analía; Baldessari, Alicia
<x xml:space="preserve">Abstract</x> The biocatalytic synthesis of a novel peptoid oligomer is reported. The oligomer is acetylated and a copolymer with polycaprolactone is prepared. These derivatives are employed for the preparation of nanoporous films. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>